The relationship between family support with physical activity activeness among elderly hypertension patients - Nailatul Khalishah; Suri Salmiyati (Universitas 'Aisyiyah Yogyakarta, 2022)
Inactivity among the elderly increases the chance of developing non-communicable diseases like hypertension. With the help of the nearest relatives, it is possible to implement the goal of physical activity in the elderly with high blood pressure, which is the key to resolving their health issues. This study aims to ascertain the connection between family support and exercise levels in senior hypertensive patients at the Gamping I Health Center. In this study, 109 elderly residents of the Gamping I Health Center served as the sample. Data were collected via questionnaires and Spearman Rank data analysis. According to the study's findings, there is a connection between family support and physical activity activeness in elderly hypertension patients.